The Prevalence of Hypothermia and its Relationship to the Mortality Rate in Burned Patients Referred to Imam Musa Kazim Hospital, Isfahan, Iran in 2014 - Davoud Yavari; Fatemeh Haddadi; Fereidon Abedini (مجله دانشکده پزشکی اصفهان, 2016)
Background: A burned patient is prone to hypothermia because of the loss of skin and severity of the burning. Timely and correct treatment of burns can minimize the damage and and improper actions can cause irreversible damage and even tend to death. This study aimed to evaluate the prevalence of hypothermia and its relationship to the mortality rate in burned patients referred to Imam Musa Kazim Hospital, Isfahan, Iran in 2014.